2020
DOI: 10.1093/mnras/staa3517
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre-main sequence stellar evolution on mid-plane snowline locations and C/O in planet forming discs

Abstract: We investigate the impact of pre-main sequence stellar luminosity evolution on the thermal and chemical properties of disc midplanes. We create template disc models exemplifying initial conditions for giant planet formation for a variety of stellar masses and ages. These models include the 2D physical structure of gas as well as 1D chemical structure in the disc midplane. The disc temperature profiles are calculated using fully physically consistent radiative transfer models for stars between 0.5 and 3 M⊙ and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 99 publications
(133 reference statements)
1
11
0
Order By: Relevance
“…It is generally expected that the C/O ratios of exoplanetary atmospheres are linked to the compositions of protoplanetary disks (e.g., Öberg et al 2011;Madhusudhan et al 2014;Mordasini et al 2016;Booth et al 2017;Cridland et al 2020;Notsu et al 2020;Miley et al 2021). In shadowed disks, the solid C/O ratio reaches the solar value in shadowed regions, similar to the outer disk (Fig.…”
Section: Diagnostic Ratios For Exoplanet Observationsmentioning
confidence: 95%
“…It is generally expected that the C/O ratios of exoplanetary atmospheres are linked to the compositions of protoplanetary disks (e.g., Öberg et al 2011;Madhusudhan et al 2014;Mordasini et al 2016;Booth et al 2017;Cridland et al 2020;Notsu et al 2020;Miley et al 2021). In shadowed disks, the solid C/O ratio reaches the solar value in shadowed regions, similar to the outer disk (Fig.…”
Section: Diagnostic Ratios For Exoplanet Observationsmentioning
confidence: 95%
“…Radial velocity surveys have revealed that the occurrence rate of detected giant planets depends upon M (e.g., Johnson et al 2010;Reffert et al 2015). The mass fraction and/or composition of planet atmospheres can give an indication as to when or where the planet was formed in a disk (Guillot & Hueso 2006;Ogihara et al 2020;Miley et al 2021). We expect that our disk evolution models also lead to the understanding of planet formation processes around IM stars.…”
Section: Implications For Planet Formationmentioning
confidence: 87%
“…as illustrated in a single value of the external UV field in Walsh et al 2013). The idea that planetary composition could link to formation locations in the disc through snow lines (Öberg et al 2011) 2020) and the time evolution of the host star luminosity (Miley et al 2021). External irradiation adds yet another factor.…”
Section: Comments On the Effect Of External Irradiation Upon Snow Linesmentioning
confidence: 99%
“…Here we do not study the time evolution of snow lines like e.g. Booth & Ilee (2019) and Miley et al (2021), but in Figure 8 we show the radius in a 100 au, 10 M ⊕ disc around a 1 M star at which the temperature drops below certain values as a function of distance from the external radiation source. The rightmost set of points represent the thermal structure of an isolated disc (placed at 100 pc in Figure 8).…”
Section: Comments On the Effect Of External Irradiation Upon Snow Linesmentioning
confidence: 99%